Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0137902
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Attitudes towards People with Intellectual Disabilities: Their Relationship with Explicit Attitudes, Social Distance, Emotions and Contact

Abstract: Implicit attitude research has expanded rapidly over the last decade and is seen as very promising as it counters biases present in much attitude research such as social desirability. However, most research in the area of intellectual disabilities has focused on explicit attitudes alone. This study examined implicit attitudes to this population and also examined their association with emotional reactions and contact, which have previously been found to have a significant influence on attitudes and stigma. A we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 61 publications
4
51
1
5
Order By: Relevance
“…Literature assessing the validity of the IAT has found little correlation between explicit attitudes and implicit attitudes, specifically regarding bias toward disability (Nosek et al, ; Pruett & Chan, ; Wilson & Scior, ). This may be expected given the social desirability of being neutral in one's attitudes toward disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature assessing the validity of the IAT has found little correlation between explicit attitudes and implicit attitudes, specifically regarding bias toward disability (Nosek et al, ; Pruett & Chan, ; Wilson & Scior, ). This may be expected given the social desirability of being neutral in one's attitudes toward disability.…”
Section: Discussionmentioning
confidence: 99%
“…This may be expected given the social desirability of being neutral in one's attitudes toward disability. In contrast, critiques of the IAT have suggested that the tool measures a single response to a visual stimuli rather than the more complex response that humans might experience (De Houwer, ; Wilson & Scior, ). De Houwer explains an example of this concept in which one may have conflicting attitudes toward a friend displaying a negative facial expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An online survey was used to collect the data. Measures used were the Attitudes Toward Intellectual Disability (ATTID) questionnaire (Morin, Crocker, Beaulieu‐Bergeron, & Caron, ) to collect self‐report data concerning explicit attitudes towards people with intellectual disabilities, and the single‐target IAT (ST‐IAT) (Wilson & Scior, ) to measure implicit attitudes to intellectual disability. The order of presenting both measures was varied randomly to test for order effects.…”
Section: Methodsmentioning
confidence: 99%
“…An adaptation of the IAT (Greenwald et al., ) was used for this study, the ST‐IAT developed by Wilson and Scior (), which showed good internal consistency of α = .70 across the 40 test trials. This used only one target concept, that is “intellectual disability,” rather than the two used in the classical IAT as there is no obvious complementary target concept to use alongside that of intellectual disability.…”
Section: Methodsmentioning
confidence: 99%